If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying hj + -2h + 5g + 4f + -20 = 0 Reorder the terms: -20 + 4f + 5g + -2h + hj = 0 Solving -20 + 4f + 5g + -2h + hj = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 4f + 5g + -2h + 20 + hj = 0 + 20 Reorder the terms: -20 + 20 + 4f + 5g + -2h + hj = 0 + 20 Combine like terms: -20 + 20 = 0 0 + 4f + 5g + -2h + hj = 0 + 20 4f + 5g + -2h + hj = 0 + 20 Combine like terms: 0 + 20 = 20 4f + 5g + -2h + hj = 20 Add '-5g' to each side of the equation. 4f + 5g + -2h + -5g + hj = 20 + -5g Reorder the terms: 4f + 5g + -5g + -2h + hj = 20 + -5g Combine like terms: 5g + -5g = 0 4f + 0 + -2h + hj = 20 + -5g 4f + -2h + hj = 20 + -5g Add '2h' to each side of the equation. 4f + -2h + 2h + hj = 20 + -5g + 2h Combine like terms: -2h + 2h = 0 4f + 0 + hj = 20 + -5g + 2h 4f + hj = 20 + -5g + 2h Add '-1hj' to each side of the equation. 4f + hj + -1hj = 20 + -5g + 2h + -1hj Combine like terms: hj + -1hj = 0 4f + 0 = 20 + -5g + 2h + -1hj 4f = 20 + -5g + 2h + -1hj Divide each side by '4'. f = 5 + -1.25g + 0.5h + -0.25hj Simplifying f = 5 + -1.25g + 0.5h + -0.25hj
| 3y-4=6 | | -16x^2-7x+10=0 | | 2.38=48 | | -16x^2-7x-1=0 | | 5(2w+3)10w=6(4w+1) | | 4+-2v+12=-8 | | x^2-36/2x-12 | | 2(1+3s)-4=6s-2 | | d=3m | | 6+3+2+2= | | (-b/3)=6 | | 5-(f+3)=5f | | 91=-4(6-6b)-5 | | 2ln(x)=ln(21) | | 17=32 | | 40=16t^2+88t | | 20=(1/4c) | | 75=3x^2-9 | | 18x+5=20x+1 | | log*(x+11)-log(2)=log*(5x+1) | | 21=-7u | | 18+5=20+1 | | 2/3x-16 | | (x/4)=3 | | 3y=8-7y-1 | | (12b-6)-(7-18b)= | | (2n^2+4n+3)(2n-3)= | | (-7x)(-1/7) | | 76.9-34.782= | | 8x+3.5=36 | | 6-10=1 | | 16x^2+7x-9=0 |